IN VITRO INHIBITION OF Bothrops asper VENOM BY ETHANOL EXTRACTS FROM Brownea ariza B. (CAESALPINIACEAE). - MACK-WEN, Viviana L.; RICO G., Leidy B.; ALARCON P., Juan C.; PEREAÑEZ J., Jaime A. (Vitae, 2011)
In Colombia, about 90% of snakebites are caused by Bothrops snakes, whose venoms cause in vivo, local and systemic disturbances, such as edema, myonecrosis, blood-clotting disorders and hemorrhage. Antivenom is the only effective treatment to manage these poisonings, but its limited action at local level and little availability in geographically isolated areas makes necessary the validation and search for therapeutic alternatives acting as an immediate resource to reduce the percent of sequels caused in these snakebites. Recent studies have reported the inhibitory action of the Brownea rosademonte (Caesalpiniaceae) extract against some local effects produced by these snakes. Therefore, in this in vitro research the inhibitory ability of the ethanol extract of leaves and bark from Brownea ariza was evaluated on proteolytic, phospholipase A2 and coagulant activities of B. asper venom, which is related with anticoagulation observed in vivo. The results showed that bark extracts inhibit phospholipase A2 activity (93,2 ± 0,4%), extend the clotting time of plasma (more than 10 minutes) and inhibit the proteolytic activity, although the latter showed lesser effects than those observed with leaves extract (77 ± 0,6% and 93,8 ± 0,6%, respectively).